Software Process Improvement during the Last Decade: A Theoretical Mapping and Future Avenues - Al-Ashmori, A. (Institute of Electrical and Electronics Engineers Inc., 2021)
Studies have been conducted in Software process improvement (SPI) for decades. These studies discussed different aspects related to SPI like small and medium enterprise (SME), critical success factors, and gamification. Some researchers conjectured that typical SPI is progressively put into the backdrop. Nevertheless, no methodical study was found utilizing bibliometric analysis of the SPI studies to further explore the related research in this domain. This paper presents a summary of the SPI recent studies collected from Web of Science database. VOSviewer was used with bibliometric analysis technique to visualize the literature contained in our study scope. As a result, six clusters were found converged on these fundamental thematic sections: SME, Capability Maturity Model Integration (CMMI), critical success factors, Agile, gamification, and knowledge management. Recommendations are provided in this paper for future research on SPI based on the present gaps. Serving as RD guidance to the SPI research community. Â© 2021 IEEE.